Comparison of validity, repeatability and reproducibility of the Peer Assessment Rating (PAR) between digital and conventional study models - Pasapula Sridhar; Sherriff Martyn; Breckon Jeremy; Bister Dirk; Abela Stefan (Sciendo, 2016)
The validity, reliability and inter-method agreement of Peer Assessment Scores (PAR) from acrylic models and their digital analogues were assessed.